Penawaran terbatas waktu Mcdonald’s ‘ini rasa kita’ pada perilaku konsumen di tiga generasi - Grace Putlia (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
The rapid development of technology has led to the habit of taking part in changes in various generations, including Indonesia which has the interest in consuming fast food. Many foreign famous brands become favorites, for them to compete. The right marketing strategy. One of the fast-food McDonald's restaurants from America that wants to continue to exist by issuing the program 'Ini Rasa Kita' which released two cultures. Western-style menus in the form of burgers, have now been made by lifting Indonesian specialties into buger rendang and balado burgers. This program uses the LTO (Limited Time Offer) system in hopes of increasing sales figures. Using qualitative research methods with case study designs, this study interviewed 15 informants from three different generations. The final results state that dominant informants are more likely to be able to receive limited time offers. In line with this, limited time offers stated that they did have anti-competitive features, however, all informants stated that limited time offer proposals could not oppose them.